Argon Plasma Coagulation in Treatment of Post Intubation Tracheal Stenosis - Jabbardarjani, Hamidreza; Kiani, Arda; Sheikhi, Negar; Masjedi, Mohammad Reza (Journal of Lasers in Medical Sciences, 2011)
INTRODUCTION: Acquired tracheal stenosis can be created by various malignant or benign causes. The most common cause of acquired non-malignant tracheal stenosis is endotracheal intubation, even for a short period. Argon plasma coagulation is a non-contact method of thermal hemostasis. Argon plasma coagulation can be used easily and fast and has low depth of penetration. METHODS: This study is single blinded. Subjects are patients with tracheal stenosis after endotracheal intubation who were selected by non-probability sampling and were studied from March 2007 to November 2009 in bronchoscopy and laser center of Masih Daneshvari Hospital, Tehran. First, for each patient, a diagnostic flexible bronchoscopy was performed to identify the type, location, and severity of the stenosis. Then, under general anesthesia, patients underwent rigid bronchoscopy. Then, with Argon plasma coagulation device (ERBE VIO 200D) the stenosis was removed as possible. After two weeks, a new PFT (pulmonary function test) was done for checking the obstructive signs. RESULTS: Of these 34 patients, 24 were asymptomatic for more than 1 year and responded to treatment(70/6%), 5 were asymptomatic for more than 10 months and less than 12 months (14/7%) and 5 did not have asymptomatic periods more than 10 months, and did not respond to treatment. In PFT follow-ups, FEV1 in all patients who were asymptomatic for more than 10 months had a significant progress; therefore, in 27 out of 29 patients at the end of the study, FEV1 was more than 90% and 2 patients had FEV1 of 70-90%. CONCLUSION: In fact, although the surgical treatment remains the main treatment of tracheal stenosis after intubation (PITS), if this method is not possible for any reason, APC is very useful as a safe and effective method.